已知:A=x的平方-7x-2,求B=2x的平方+4x-3,求2A-3B.
举一反三
- 已知f(X)=X平方-1求f(2)
- $(-x-1)(x^{4}+2x^{3}-x^{2}-4x-2)+(x+2)(x^{4}+x^{3}-x^{2}-2x-2)$的结果是( )。 A: $x^{2}-2$; B: $x^{3}-x^{2}-1$; C: $2x^{3}-4x-2$; D: $x^{4}+3x-2.$
- 函数\(y = {x^{ - 4}}{\rm{ + }}2{x^3} - 2x\)的导数为( ). A: \(4{x^3} + 6{x^2} - 2\) B: \( - 4{x^{ - 5}} + 6{x^2} - 2\) C: \( - 4{x^{ - 3}} + 6{x^2} - 2\) D: \( - 4{x^3} + 6{x^2} - 2\)
- (1)2x平方+3x=3,(2)x平方一2x+1=25(3)x(2x一5)=4x—10(4)x平方+5x+7=3x十11(5)1—8x+16x平方=2一8x请各帮一下我一定会回赞的
- 已知\( y = {x^3}\cos 2x \),则\( y'' \)为( ). A: 0 B: \( 6x\cos 2x{\rm{ + }}12{x^2}\sin 2x - 4{x^3}\cos 2x \) C: \( 6x\cos 2x - 12{x^2}\sin 2x{\rm{ + }}4{x^3}\cos 2x \) D: \( 6x\cos 2x - 12{x^2}\sin 2x - 4{x^3}\cos 2x \)